2010
DOI: 10.1074/jbc.m110.169532
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Spectroscopic Characterization of the Human Mitochondrial Amidoxime Reducing Components hmARC-1 and hmARC-2 Suggests the Existence of a New Molybdenum Enzyme Family in Eukaryotes

Abstract: The mitochondrial amidoxime reducing component mARC is a newly discovered molybdenum enzyme that is presumed to form the catalytical part of a three-component enzyme system, consisting of mARC, heme/cytochrome b 5 , and NADH/FADdependent cytochrome b 5 reductase. mARC proteins share a significant degree of homology to the molybdenum cofactorbinding domain of eukaryotic molybdenum cofactor sulfurase proteins, the latter catalyzing the post-translational activation of aldehyde oxidase and xanthine oxidoreductase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
158
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(176 citation statements)
references
References 45 publications
18
158
0
Order By: Relevance
“…Although soluble CYB5R3 can support the amidoxime reductase activity in vitro together with truncated soluble MOSC2 and CYB5B (13,14), we were unable to confirm its involvement in the adipocyte cell system. This is despite the fact that we identified CYB5R3 as one of the proteins that was crosslinked by the radiolabeled substrate in the OMM and might possibly reflect not direct binding of the substrate to CYB5R3 but background caused by nonspecific cross-linking background.…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…Although soluble CYB5R3 can support the amidoxime reductase activity in vitro together with truncated soluble MOSC2 and CYB5B (13,14), we were unable to confirm its involvement in the adipocyte cell system. This is despite the fact that we identified CYB5R3 as one of the proteins that was crosslinked by the radiolabeled substrate in the OMM and might possibly reflect not direct binding of the substrate to CYB5R3 but background caused by nonspecific cross-linking background.…”
Section: Discussionmentioning
confidence: 38%
“…MOSC1 was like its homolog MOSC2 up-regulated in differentiated adipocytes, but down-regulation of MOSC1 in these cells did not affect the amidoxime reductase activity. MOSC1 has previously been shown to be able to reduce amidoximes to amidines in vitro (13,14). The reason for this discrepancy is unclear, but in the in vitro system the amidoxime reductase activity was reconstituted with recombinantly expressed truncated and soluble components CYB5B and CYB5R3 and MOSC1 or MOSC2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xanthine dehydrogenase, another important Moco enzyme, catalyzes the conversion of hypoxanthine to xanthine and further to uric acid (Hille 2005). Aldehyde oxidase catalyzes the hydroxylation of various compounds (Garattini et al 2009), while mARC was identified as a general detoxifying and pro-drug metabolizing enzyme with yet unknown physiological substrates (Wahl et al 2010).…”
Section: Introductionmentioning
confidence: 99%